Financial management of student organizations in UP Visayas - Baga, Wendy; Bitong, John Rey; Estela, Shariz Valerie; Junsan, Kent Jhon; Rebuta, Jean
Student organizations have played an important role in developing holistic individual as well as a complete package of future professionals that would eventually lead and serve the nation. Student organizations may differ in types, nature, structure and objectives but one unifying factor across all these diversities are their need for an efficient financial management strategy through the use of accounting practices. This study presents an overview of the current financial management practices of student organizations in the University of the Philippines Visayas followed by an evaluation of the appropriateness of such practices. Results of the survey interview revealed certain strong and weak points of organizations in the different aspects of financial management namely budgeting, bookkeeping, cash flow management, financial reporting, internal control and auditing and monitoring. Through frequencies and percentages, data analysis showed that majority of student organizations have problems with budgeting, bookkeeping, internal control and auditing and monitoring. On a positive note, student organizations are relatively keen on their cash flow management practices. However, challenges still remain on the efficiency and effectiveness of the financial management practices of student organizations in UPV considering that not all possible factors such as the size and structure of organizations are incorporated in this study.